Estratégia de competição empresarial na construção civil paraense da Copala Industrias Reunidas S/A - RUFFEIL JUNIOR, Simão Massud (Universidade Federal do Pará, 2011)
This dissertation is based on the analysis of competitive strategy adopted in the market of iron bar for civil construction in Belém, capital of Pará, by COPALA INDUSTRIAS REUNIDAS S/A. So, there is interest in evaluate the possibilities of the company in the sense o f staying actuating with success in the sector, in which weighs the contestant carried out by metallurgies of great deportment, of which interests are from national and international encompassing. Search were realized considering the steel market of de civil construction of an ample way, being consulted constructors, businessmen and consumers of that material. Like wise, the proper COPALA was object of evaluation as well as acquirer of raw material to the steel manufacture, as how producer and seller of the product .